CLINICAL CHARACTERISTICS OF BREAST CANCER WITH STEROID RECEPTORS EXPRESSION AND HER2 AMPLIFICATION - F. V. Moiseenko; V. F. Semiglazov; T. Yu. Semiglazova; A. A. Bogdanov; I. E. Eliseev; A. O. Ivantsov; N. А. Knyasev; I. N. Terterov; А. A. Kornev; M. V. Dubina (Креативная хирургия и онкология)
Since the  middle of the  previous  century  the  heterogeneity of breast cancer  became absolutely evident. This assumption was historically based on differences in clinical behavior and sensitivity to therapy. Treatment approach nowadays is based  primarily on clinical and morphological prognostic and predictive markers. Among morphologically derived markers the most  important are estrogen and progesterone receptors and HER2. Interestingly that tumors with expression of estrogen receptors and/or progesterone receptors that  showed also hyperexpression or amplification of HER2 have very poor outcome and low sensitivity to  all therapeutic  approaches.  Therefore we  want   to  summarize the  existing  clinical information that  is relevant to this topic.